In silico analysis to explore the therapeutic potential of propolis-derived small molecules as matriptase inhibitors to suppress breast cancer growth and metastasis - Muhammad Bilal Azmi; Han Yu; Arisha Sohail; Uzma Asif; Syed Danish Haseen Ahmed; Shamim Akhtar Qureshi; Mohnad Abdalla (PLoS ONE, 2025)
Breast cancer is a major cause of death in women, and various drug therapies are used for its treatment. However, current therapies have many side effects and limitations. Propolis, a resinous product of bee hives, possesses a variety of biological activities, including anticancer and chemo-protective properties. The present study aimed to investigate the potential suitability of propolis-derived compounds to inhibit matriptase (MT-SP1), a potential protein target for breast cancer treatment, through comprehensive computational analysis. The MT-SP1 protein structure (PDB ID: 1EAX) was retrieved, energy-minimized, and validated. Five propolis-derived compounds with the highest binding energies to MT-SP1 were selected after virtual screening. Molecular docking of these selected ligands revealed binding energies ranging from -8.4 to -9.1 kcal/mol. Stable complex formation was validated by an additional 250 ns of molecular dynamics simulations. The HOMO-LUMO and DFT characteristics provided further evidence of the chemical reactivity and stability of these five ligands at the MT-SP1 active site. Screening of compounds for drug-likeness, pharmacokinetics (ADMET profiles), and toxicity identified two promising small molecules (PubChem IDs of ligands 72307 and 129827386) as potential drug candidates for inhibiting MT-SP1. However, experimental validation through in vitro or in vivo studies is necessary to confirm these computational findings and explore their therapeutic potential for breast cancer treatment.